Immunotherapies for Neurodegenerative Diseases - Mortada, Ibrahim; Farah, Raymond; Nabha, Sanaa; Ojcius, David M.; Fares, Youssef; Almawi, Wassim Y.; Sadier, Najwane Said (Frontiers in Neurology, 2021)
The current treatments for neurodegenerative diseases are mostly symptomatic without affecting the underlying cause of disease. Emerging evidence supports a potential role for immunotherapy in the management of disease progression. Numerous reports raise the exciting prospect that either the immune system or its derivative components could be harnessed to fight the misfolded and aggregated proteins that accumulate in several neurodegenerative diseases. Passive and active vaccinations using monoclonal antibodies and specific antigens that induce adaptive immune responses are currently under evaluation for their potential in the development of immunotherapies. In this review, we aim to shed light on prominent immunotherapeutic strategies being developed to fight neuroinflammation-induced neurodegeneration, with a focus on innovative immunotherapies such as vaccination therapy